PsyCap and Performance: Wellbeing at Work as a Mediator. (June 2020) - Imran, Mohammad; Shahnawaz, Mohammad Ghazi
This article investigated whether wellbeing at work mediates the relationship between psychological capital (PsyCap) and performance. It also assessed the validity of the widely used measure for PsyCap—the psychological capital questionnaire (PCQ)-24, in the Indian work context. A sample of 225 employees from different private sector industries filled up the questionnaires, measuring PCQ-24, wellbeing (index of psychological well-being at work) and performance (Greene–Shortridge scale of job performance). The scales were validated using confirmatory factor analysis, and the mediation model was tested using Hayes PROCESS macro. The results showed that PCQ-24 mediates the association between PsyCap and performance. PsyCap influenced job performance by way of augmenting wellbeing at work. The PCQ-24 was also found to be a valid measure in the Indian work context with a few modifications. The results were discussed using cognitive positive appraisal of work-related factors, conservation of resources theory (COR) and broaden and build theory.